Correlation Between Community Knowledge Level of River Ecosystem Services and Littering Behavior in Belawan Hilir Sub-watershed - Bejo Slamet; Masrizal Saraan; Harry Kurniawan; Ulfa, Mariah (Talenta Publisher, 2022)
Belawan watershed is one of the watersheds that have a primary role in North Sumatra Province. The flow of the Belawan watershed crosses 2 (two) regencies/cities, i.e., Deli Serdang Regency and Medan City. In more detail, Medan City is located in the Belawan Hilir Sub-watershed. Several main rivers in Medan have been polluted and shallowed, as a result of people's habit of littering the river. People who live around the Belawan watershed have a significant role in the sustainability of the river and its ecosystem services. This study aims to analyze the level of community knowledge of river ecosystem services in the Belawan Hilir sub-watershed and to measure the correlation between the community knowledge level and the behavior of river littering. The respondents were sampled using Simple Random Sampling, while the number of samples was calculated using the Slovin formula. Data was collected through structured interviews by compiling a list of questions (questionnaires). The correlation between community knowledge levels and behavior of river littering was determined using spearman correlation analysis. The community knowledge level was 63% (good category). There was a moderate-positive correlation between the community knowledge level and the behavior of river littering (0.512 correlation coefficient). Community awareness can be increased through online-based socialization using social media or by providing more waste management training programs.